Analysis and Use of Figures of Speech - Regmi, Lok Raj (Journal of NELTA Surkhet, 2015)
Poetry, a form of literature, displays varieties of language use through figures of speech, the rhetorical devices. There are two views for and against the use of such rhetorical devices in language teaching. One of the views shows its strong resentment in using such figures of speech and does not find the space of them in language teaching whereas the next speaks in favour of using them in language teaching if the texts are wisely selected. It is the judicious or creative use of figures of speech. A language teacher tries to look at them from language teaching point of view. This writing primarily analyzes the representative figures of speech, states some examples with their language features and ultimately justifies how figures of speech support language teaching and learning. Journal of NELTA Surkhet Vol.4 2014: 76-80